Avaliação microbiológica de Sushis e sashimis comercializados na cidade de Maceió-AL. - Pereira, Waleria Dantas (2008)
The fishes are foods very propitious to deterioration, for have the pH next to the neutrality, the water high activity and the elevated content of nutritious. For they reflect the contamination of the springs and to are excessively manipulated, without suffering no thermal treatment when used to prepare sushis and sashimis, represent potential risk of transmit alimentary origin diseases. Thus this search objective to evaluate the microbiological quality of sushis and sashimis commercialized in Maceió-Al, to alert the sanitary authorities and the consumers on the sanity conditions of these victuals. They were going collected 60 samples, being 30 (thirty) of sushis and 30 (thirty) of sashimis, commercialized in 05 (five) specialized restaurants and 05 (five) not specialized restaurants in japanese food, in which searched coliforms to 35ºC, coliforms to 45ºC, E. coli, Salmonella spp, S. aureus and B. cereus, according with analysis methods by APHA (2001) and FDA (2005). The results demonstrated isolation of all of microrganisms analyzed, indicating that the raw material is bad quality, it suffer imperfect manipulation or prepare and it is inadequate distribution in time or meals temperature. A total of 90% of the sushis and 93,33% of sashimis contained enumerations of coliformes to 45ºC, presence of Salmonella spp or countings of Sthapylococcus coagulase positive above of the certain standards by RDC n.º 12 of ANVISA (2001). Being thus, considering microrganisms pathogenic potential identified in the samples, it suggests that urgent measures, as the Production Good Practices implantation, be implemented in the sushis and sashimis productive process in the city of Maceio, so that the alimentary safety be guaranteed.